KUALITAS PELAYANAN PRAMUWISATA DI ISTANO BASA PAGARUYUNG - Muhammad Kamal; Syofia Achnes (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This research is to know about the quality of service guides in Istano Basa Pagaruyung Tanah Datar regency of West Sumatra Province. The study aims to know how the quality of service guides in Istano Basa Pagaruyung District Tanah Datar West Sumatra Province. This research uses a descriptive method quantitative to examine the issues raised. The sample used in this research is 100 respondents taken by accidental sampling. While data collection techniques in this study using observation, questionnaires and interviews. Based on the results of research that has been done, that the quality of service guides in Istano Basa Pagaruyung Tanah Datar regency of West Sumatra Province still low and needs to be improved again. Viewed by five dimensions, namely dimensions tangible, reliability, responsiveness, assurance and empathy. Keywords: Service Quality, Tangible Dimension, Reliability Dimension, Dimension Responsiveness, Dimension Assurance, Dimension Empathy.